Important factors affecting adjuvant treatment decision in stage IA breast cancer patients in Turkey - Öven Ustaalioğlu, Bala Başak; Bilici, Ahmet; Erkol Yılmaz, Burçak; Aliustaoğlu, Mehmet; Şeker, Mesut; Vardar, Fügen; Gümüş, Mahmut (S. Karger AG, 2014)
Introduction: In Turkey, the gene expression profile test is not standard, so adjuvant treatment is planned according to clinicopathological factors. Therefore, we retrospectively analyzed important parameters that affect the decision on adjuvant chemotherapy, and also factors related to survival in stage IA breast cancer patients in Turkey. Methods: We retrospectively evaluated 347 stage IA patients. The relationship between the clinicopathological parameters and adjuvant chemotherapy was analyzed. Results: The median age and follow-up time were 52 years (range: 25-86) and 22.6 months (range: 1-113), respectively. The 5-year disease-free survival (DFS) and overall survival (OS) rates were 87.9% and 98.7%, respectively, but the median DFS was not reached. Age, estrogen receptor (ER) status, human epidermal growth factor receptor 2 (HER2) status, and the presence of triple-negative breast tumor (TNBC) were related to DFS, and lymphovascular invasion (LVI), perineural invasion (PNI), HER2 status, the presence of TNBC, and recurrence were related to OS (p < 0.05). Furthermore, age, menopausal status, multicentricity, grade, tumor size, necrosis, ER, the presence of TNBC, and HER2 were found to be related to adjuvant therapy decision (p < 0.05). All these parameters, in addition to LVI and PNI, were independent factors for chemotherapy by logistic regression analysis. Conclusions: In decisions about adjuvant therapy in stage IA breast cancer patients, clinicopathological factors should be kept in mind.
Keywords: Adjuvant Therapy; Breast Cancer; Chemotherapy; Stage IA